2013
DOI: 10.1097/pai.0b013e318279f9ee
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of TLE1 Expression in Unclassified High-grade Sarcomas for the Diagnosis of Synovial Sarcoma

Abstract: Expression of the transducin-like enhancer of split 1 (TLE1) by immunohistochemistry (IHC) has been widely used as a biomarker for the diagnosis of synovial sarcoma. Although TLE1 expression can be identified in more than 90% of synovial sarcomas, positive staining has been reported in up to one third of nonsynovial sarcomas, including peripheral nerve sheath tumors and neoplasms of fibrous and adipose tissues. The low specificity of this test in soft tissue tumors raises concern on its clinical application as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…It was also found that no significant difference existed in TLE‐1 staining among the different subtypes of synovial sarcoma ( P ‐value >0.05). In other words, our study supports the use of TLE‐1 staining for the diagnosis of poorly differentiated synovial sarcoma …”
Section: Discussionsupporting
confidence: 81%
“…It was also found that no significant difference existed in TLE‐1 staining among the different subtypes of synovial sarcoma ( P ‐value >0.05). In other words, our study supports the use of TLE‐1 staining for the diagnosis of poorly differentiated synovial sarcoma …”
Section: Discussionsupporting
confidence: 81%
“…The identification of the corepressor TLE1 as an SS18-SSX interacting protein is also significant because expression profiling experiments have identified TLE1 among the most consistently highly expressed genes in primary synovial sarcoma specimens (29, 35). Incidentally, nuclear expression of TLE1 is readily detectable by immunohistochemistry on formalin-fixed paraffin-embedded tissues, and its diagnostic value for synovial sarcoma has been confirmed (36, 37), leading to its adoption into clinical use.…”
Section: The Ss18-ssx Fusion Oncogenementioning
confidence: 99%
“…TLE1 is involved in the Wnt/β-catenin signaling pathway, which is important in synovial sarcomas, and in the nuclear factor κB (NF-κB) pathway that regulates inflammation [891011]. TLE1 is a highly sensitive immunohistochemical marker for the diagnosis of synovial sarcoma; however, TLE1 expression is not specific for synovial sarcoma, as it is expressed in other tumor types [1213]. Knockdown of TLE1 in fibroblasts and synovial cells enhances the cytotoxic effect of chemotherapy, which suggests that TLE1 could be a promising therapeutic target for selectively treating synovial sarcoma without damaging healthy tissue [14].…”
Section: Introductionmentioning
confidence: 99%